2018
DOI: 10.1186/s12964-018-0276-4
|View full text |Cite
|
Sign up to set email alerts
|

A role for RASSF1A in tunneling nanotube formation between cells through GEFH1/Rab11 pathway control

Abstract: BackgroundBy allowing intercellular communication between cells, tunneling nanotubes (TNTs) could play critical role in cancer progression. If TNT formation is known to require cytoskeleton remodeling, key mechanism controlling their formation remains poorly understood.MethodsThe cells of human bronchial (HBEC-3, A549) or mesothelial (H2452, H28) lines are transfected with different siRNAs (inactive, anti-RASSF1A, anti-GEFH1 and / or anti-Rab11). At 48 h post-transfection, i) the number and length of the nanot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(66 citation statements)
references
References 86 publications
(148 reference statements)
6
60
0
Order By: Relevance
“…The authors have previously demonstrated that the loss of RASSF1A expression leads to the inappropriate activity of YAP, the subcellular localization of which becomes preferentially nuclear and coincides with an increase in the transcription of several target genes [4,5,28]. Some IAPs, proteins acting as negative apoptosis regulators by inhibiting the activity of several caspases [29], could also be the transcriptional targets of YAP as shown in drosophila [13].…”
Section: Rassf1a Depletion Coincides With Strong Yap-dependent Iap-2 mentioning
confidence: 98%
“…The authors have previously demonstrated that the loss of RASSF1A expression leads to the inappropriate activity of YAP, the subcellular localization of which becomes preferentially nuclear and coincides with an increase in the transcription of several target genes [4,5,28]. Some IAPs, proteins acting as negative apoptosis regulators by inhibiting the activity of several caspases [29], could also be the transcriptional targets of YAP as shown in drosophila [13].…”
Section: Rassf1a Depletion Coincides With Strong Yap-dependent Iap-2 mentioning
confidence: 98%
“…In addition, several teams describe that TNTs also allow tumor cells to reprogram the healthy neighboring cells to make them more conducive to the formation of a tumor niche. Interestingly, not only a hostile environment (inflammation, hypoxia, and inadequate pH) enhances TNT formation [4,[8][9][10][11], but also TNTs could contribute to the escape of the cells from the cell death induced by apoptosis [10,[12][13][14]. On the other hand, TNTs convey resistance to chemotherapy by exporting the mitochondria [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest to vision researchers is the role of the tumor suppressor gene, RASSF1A, in uveal melanomas [115]. RASSF1A binds cytoskeletal proteins such as actin and microtubules, playing an important role in TNT formation, cell cycle regulation, and apoptosis to maintain cellular homeostasis [35,111]. Loss of RASSF1A gene expression is observed in certain cancers, including uveal melanomas in the eye [115,116].…”
Section: Cancermentioning
confidence: 99%
“…Loss of RASSF1A gene expression is observed in certain cancers, including uveal melanomas in the eye [115,116]. In malignant mesothelial cell lines, downregulation of RASSF1A increased the number of TNT connections, while overexpression decreased the TNT number and length [35]. Thus, increased TNT-mediated communication concomitant with downregulation of RASSF1A appears linked to cancer progression.…”
Section: Cancermentioning
confidence: 99%
See 1 more Smart Citation